The global response and unmet actions for HIV and sex workers - Shannon,K; Crago,A-L; Baral,S; Bekker,L-G; Kerrigan,D; Decker,M; Poteat,T; Wirtz,A; Weir,B; Boily,MC; Butler,J; Strathdee,S; et al. (Lancet, 2018)
Female, male, and transgender sex workers continue to have disproportionately high burdens of HIV infection in low-income, middle-income, and high-income countries in 2018. 4 years since our Lancet Series on HIV and sex work, our updated analysis of the global HIV burden among female sex workers shows that HIV prevalence is unacceptably high at 10·4% (95% CI 9·5–11·5) and is largely unchanged. Comprehensive epidemiological data on HIV and antiretroviral therapy (ART) coverage are scarce, particularly among transgender women. Sustained coverage of treatment is markedly uneven and challenged by lack of progress on stigma and criminalisation, and sustained human rights violations. Although important progress has been made in biomedical interventions with pre-exposure prophylaxis and early ART feasibility and demonstration projects, limited coverage and retention suggest that sustained investment in community and structural interventions is required for sex workers to benefit from the preventive interventions and treatments that other key populations have. Evidence-based progress on full decriminalisation grounded in health and human rights—a key recommendation in our Lancet Series—has stalled, with South Africa a notable exception. Additionally, several countries have rolled back rights to sex workers further. Removal of legal barriers through the decriminalisation of sex work, alongside political and funding investments to support community and structural interventions, is urgently needed to reverse the HIV trajectory and ensure health and human rights for all sex workers.